Long‐term effects of flow regulation by dams simplify fish functional diversity. (11th January 2018) - Oliveira, Anielly G.; Baumgartner, Matheus T.; Gomes, Luiz C.; Dias, Rosa M.; Agostinho, Angelo A.
Abstract: The long‐term impact of river regulation on fish functional diversity by a dam immediately upstream from the upper Paraná River floodplain, Brazil, was evaluated. It was expected that the resulting alterations in natural flow, downstream from the dam, would negatively impact fish species, resulting in a functional simplification of the ichthyofauna. In addition, this effect was expected to be more pronounced in the directly affected main channel of the Paraná River than in its tributaries, the Baía and Ivinhema rivers. Fish were sampled before (pre) and after (post) dam closure (the intervention). The functional traits used were diet, habitat use, mouth position, migration, parental care, internal fertilisation and maximum total length. Differences in trait composition between periods (pre and post) were tested using a PERMANOVA main‐test. An indicator value analysis (IndVal) was applied to identify which traits significantly increased or decreased in abundance after the intervention. The indexes used were functional richness (FRic), Rao's quadratic entropy (FDQ ) and functional redundancy (FRed). The intervention analysis based on linear models for time series was used to evaluate differences in these indexes over time. Traits most representative during pre‐intervention were large‐bodied species with long reproductive migrations, pelagic, with subterminal and superior mouths, and herbivorous. Traits most representative during the post‐intervention were omnivorous species, with parental care, benthopelagic and insectivorous, which typically characterise fishes that inhabit stable environments. FRic decreased in Paraná and Baía rivers after the construction of the dam. However, the Ivinhema River showed an increase in mean FRic in the post‐intervention period. FDQ decreased substantially in all three rivers, while FRed increased. The combined results of FRic, FDQ and FRed corroborate the functional simplification hypothesis expected from flow regulation by dams on functional diversity. As expected, the most pronounced simplification occurred in the Paraná River. Therefore, hydroelectric power plants can act as environmental filters strongly selecting functional traits of the downstream fish fauna, generating long‐lasting impacts on ecosystem functioning and services.